The Influence of Simmental Cow Build Types on Productive Properties (Eurasian Journal of Research, Development and Innovation, 2022)
The degrees of milk productivity, the nature of lactation, the yield of milk production per 100 kg of live weight, and the amount of payment for feed by milk production of Simmental cows are all linked to the kind of building, according to the study. Dairy cows produce 672.5 and 958.5 kg of milk per lactation, respectively, with 4 percent milk yields of 507.4 and 735.4 kg. Milk yields 164.9 and 228.7 kg more per 100 kg of living weight than its dairy-meat and meat-dairy counterparts, respectively. In dairy cows, the highest monthly milk yield was found in the third month of lactation, while in dairymeat and meat-dairy cows, the highest monthly milk yield was recorded in the second month of lactation. This suggests that dairy cows lactate more evenly than other breeds of cows. The results show that using dairy cows for milk production is quite efficient.